Arbetsmiljöns påverkan inom detaljhandeln. En studie om hur vakanta arbetstjänster påverkar personalomsättning, försäljning & kundupplevelse - Erhardsson, Viktoria; Skagerström, Amanda (My University, 2022)
This report follows a study of how the work environment interfaces with the everyday life of a coworker in retail. The current problem that IKEA Uddevalla is facing is the appearance of vacancies and that these vacancies are not replaced when they occur. How the vacancies affect the work environment, turnover of staff, co-workers, customers and profit is not known by IKEA today. In the current situation IKEA takes staff from the department Saluhallen when it is needed at other departments. This is because IKEA does not think having vacancies at Saluhallen affects the profit as much as it does at, for example, the kitchen department. The aim of the study is to find out how the amount of co-workers influences the work environment and hence the profit at Saluhallen. The study resulted in a couple of elements that keeps the staff motivated at work in the retail industry and also some elements that keeps them going to their job and not wanting to quit their positions. The most common answer from the staff was that they consider the amount of staff being too low and as a result of this their work feels more stressful. A stressful environment leads to a higher staff turnover and a lower quality of the customer service. The report identified four different elements that are affected by the lack of staff; the well being of the staff, how the appearance of the department appeals to the customers, the knowledge of the products and the customer service. All the elements above affect the profit. Despite IKEA saving the salary of the vacant position, the study showed that it is more profitable to replace vacant positions immediately. This can be explained by the advantageous outcome of a fully staffed department. The staff is healthy which decreases the staff turnover, the staff have more time for additional sales and purchases are not left out because of lack of staff. Altogether the result is that by replacing vacant positions, Saluhallen could increase their profit with 240 065 swedish crowns.
Keywords: staff turnover, motivation factors, work environment, vacancies, profitability